SOME ASPECTS OF PUBLIC ADMINISTRATION AND PUBLIC BUDGETING OF THE SLOVAK REPUBLIC - Džuňová, Jana (Review of European and Comparative Law, 2017)
Article presents characteristics of public administration of the Slovak Republic. The first part of article is focused on structure of public administration, with an emphasis on territorial self-government. The second part of article is focused on the budget of territorial self – government, with some aspects of fiscal decentralization. At the end of issue are presented the main conclusions, with the proposal for improvement.